Multi-element fingerprint to discriminate the geographical origin of Ruditapes philippinarum (Adams & Reeve, 1850) of the Tagus and Sado estuaries - Vieira, Soraia Vanessa Teixeira de Aguiar (2022)
Mestrado em Gestão e Conservação de Recursos Naturais - Instituto Superior de Agronomia / Universidade de Évora